New Topologies of a Lossless Grounded Negative Inductor Using Single CDBA - Jarwal D.K.; Baral K.; Singh A.K.; Singh P.K.; Jit S. (My University, 2025)
In this paper, two new types of lossless grounded negative inductance simulator circuit topologies are proposed. The proposed topologies utilize one current differencing buffered amplifier (CDBA) block and some passive components. The active block CDBA incorporates advantage of both current mode (CM) and voltage mode (VM) which gives flexibility to operate both in CM and VM. The first topology is conditional and the second one is unconditional lossless grounded negative inductor. At last, a second order sinusoidal oscillator circuit and a band pass filter are constructed using the proposed lossless negative inductance simulator. PSPICE simulation results are included to verify theory. © 2019 IEEE.